If it's not what You are looking for type in the equation solver your own equation and let us solve it.
116+7x=55-2x
We move all terms to the left:
116+7x-(55-2x)=0
We add all the numbers together, and all the variables
7x-(-2x+55)+116=0
We get rid of parentheses
7x+2x-55+116=0
We add all the numbers together, and all the variables
9x+61=0
We move all terms containing x to the left, all other terms to the right
9x=-61
x=-61/9
x=-6+7/9
| 116+7x=55-2x | | 21.8=6.4x-3 | | -1/3(18+6x)=-1/2(4x+12) | | 2*x+3=5*x−7 | | 7x-4=-3x+5+10x | | 3z+2=2z+3 | | -11=x/5-6 | | 100=4(3e-2)+8(1+e) | | 4/5(5x-15)=1 | | 0.09(4+m)=1.08 | | 13v=20v-35 | | 13v=20v-35 | | 13v=20v-35 | | 35-3z=2z | | 41=w+26 | | 2v+7=2+v | | -2/3(6x-12)=66 | | (85-x)=4x | | 6p^2-2p-20=0 | | 3u/2=30 | | (85-x)=4x | | 20=2(p+5) | | (85+x)=4x | | (85+x)=4x | | (85+x)=4x | | 4(f+3)=20 | | (85+x)=4x | | 4(f+3)=20 | | 4(f+3)=20 | | 4-(q-4)=20 | | 4-(q-4)=20 | | 5a-36=3a |